2016
DOI: 10.1080/0158037x.2016.1141762
|View full text |Cite
|
Sign up to set email alerts
|

Experiential and outdoor education: the participant experience shared through mind maps

Abstract: This paper describes an analysis of mind maps capturing the experiences of the participants in an experiential and outdoor education course. The method of mind mapping is usually limited to a quantitative scoring analysis and comparative content analysis of concepts. As a consequence, the visual elements of the information are usually ignored, but to analyze the holistic information, it is necessary to analyze its visual elements. This intention underlines this study of five chosen pairs of mind maps made by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…Czech outdoor education has its roots in the early twentieth century. In spite of political restrictions, this type of education persisted until the democratic revolution in 1989, mainly in the form of summer camps and outdoor residential programs focused on developing inter- and intra-personal competence (Jirásek & Turcova, 2017 , Jirásek et al, 2016 , Kudláček et al, 2009 ). Since its beginnings in the non-formal education movement, environmental education has evolved into a closely cooperating network of environmental education centers offering both school-based and residential outdoor programs.…”
Section: Introductionmentioning
confidence: 99%
“…Czech outdoor education has its roots in the early twentieth century. In spite of political restrictions, this type of education persisted until the democratic revolution in 1989, mainly in the form of summer camps and outdoor residential programs focused on developing inter- and intra-personal competence (Jirásek & Turcova, 2017 , Jirásek et al, 2016 , Kudláček et al, 2009 ). Since its beginnings in the non-formal education movement, environmental education has evolved into a closely cooperating network of environmental education centers offering both school-based and residential outdoor programs.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that visual elements can be ignored when including smart maps in learning. The use of symbolic elements for informa on percep on should be ensured to avoid such an approach (Jirásek et al 2016). The possibility of visual percep on of informa on should be provided when learning a foreign language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kresba se dá bezpochyby výzkumně aplikovat i u dospělých, byť je prozatím v českém pedagogickém výzkumu její využití v roli subjektivní percepce sdílené formou výtvarných artefaktů mimořádně nízké (navíc sdílené s mezinárodní komunitou, nikoli prostřednictvím českých pedagogických periodik), např. při hlubším porozumění vlivu zimního táboření v rámci neformální edukace (Jirásek et al, 2016;Jirásek & Hanuš, 2022) či v propojení kresby s osobnostní typologií MBTI v roli specifikace studentů vybraného vysokoškolského oboru (Jirásek et al, 2021).…”
Section: Epistemologické Zakotvení Využití Obrazu Ve Výzkumuunclassified